(untitled) (AYUSHDHARA, 2024)
Septic arthritis is a condition in which an inflammation of a joint that’s usually caused by bacterial infection. Typically, septic arthritis affects one large joint in the body. On observing pathological changes and clinical features, septic arthritis nearly corresponds with Krostukasheersha caused due to vitiation of Vata and Rakta dosha. A 45 years female patient c/o pain and swelling in left knee joint since 1½ year associated with burning sensation, raise of temperature and heaviness of the limb, diagnosed as septic arthritis or synovitis. The patient treated with Godhumadi Upanaha, Basti, and Rakthamokshana along with some oral medications. A patient was recovered from her illness and significant improvement occurs on overall symptoms and general well-being after the completion of the treatment. Management of emergency conditions like septic arthritis through Ayurveda has immense potential.